Banality of Political Communication in Indonesian Presidential Election Contestation - Widodo Agus Setianto (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
This study aims to describe the banality of discourse through the deconstruction of discourse on the discourse of political actors through viral political communications in online media. Through discourse deconstruction, an overview of the discourse meaning is obtained, and the discourse intent under study is revealed. This study uses a constructivist paradigm. The research uses linguistic and structural methods, objectives hermeneutic, and social semiotics. The results of the study show that there is power-oriented vulgarity with vulgar language, low political morality, political egoism, and political justification. This research shows that symbolic violence in political communication.